Rhyme and Reason; a Compilation of Verses, Rhymes and Senses - Dom (Salt Lake City, UT : Project Gutenberg, 2004)
"Rhyme and Reason; a Compilation of Verses, Rhymes and Senses by Dom" is a collection of poetic works likely written in the early 21st century. This compilation showcases a variety of themes ranging from the beauty of nature and personal reflection to the complexities of life and human emotions. The verses often convey deep philosophical insights wrapped in lyrical expressions. The book consists of numerous individual poems, each exploring different facets of life, hope, and the passage of time. In pieces like "Risking for a Sign," the author emphasizes the essence of taking risks in pursuit of one's aspirations, while "Year$1 (Bs End" reflects on the cyclical nature of time and the sentiments tied to farewells and new beginnings. Other poems, such as "Seaside Sunrise" and "Wanderer's Notation," illustrate vivid imagery and emotional depth, prompting readers to ponder their own experiences and connections to the world around them. Overall, the collection serves not only as a literary exploration but also as an invitation for introspection and reflection on life's inherent journey. (This is an automatically generated summary.)s
Release date is 2004-03-01
Keywords: Poetry